EKSPRESI NILAI ESTETIKA DALAM TETANDINGAN BANTEN GEBOGAN - I Wayan Rudiarta; I Made Rajendra (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
This study aims to analyze the banten gebogan which has undergone a change towards modernization which explores more artistic and aesthetic values. Gebogan is a form of offering used by Hindus in a yadnya ceremony. Gebogan has been used for generations by Balinese Hindus as a means of panning to resemble a mountain. This study uses a qualitative approach with data obtained through library research and documentation studies. The data that has been collected is then analyzed through data reduction, data presentation to conclusions and the data is presented in the form of an exploratory narrative. The results of the study show that banten gebogan is one of the offerings used by Hindus to show gratitude to Ida Sang Hyang Widhi Wasa, so traditionally they use various local ingredients/facilities. But in rhythm with the times, gebogan has changed towards a more aesthetically pleasing shape, materials/suggestions used as well as in terms of function. The changes that have taken place are based on a number of things, such as the form of devotion to Ida Sang Hyang Widhi Wasa, expressions of art and aesthetics and the people wanting something practical, effective and efficient. Changes in gebogan to be more aesthetic and undergoing modernization are manifestations of devotional service which began with the presence of the intention to make ceremonial means full of beauty (sundaram), without forgetting the principle of truth (Satyam) and the principle of holiness (sivam).Keywords: Aesthetic, Gebogan, Hindu